Dynamics of the expansion and appropriation of natural resources on the frontiers of the Brazilian and Venezuelan Amazon: a “link” between primitive accumulation and the development of capital - Cutrim Carvalho, André; Petit, Pere (Espacio Abierto, 2023)
On the frontiers of the Brazilian Amazon and the Venezuelan Amazon, the growing increase in human populations has constituted a substantial part of the ecosystems in which they live. The scale and intensity of human occupation has caused a series of significant and differentiated environmental impacts not only on a local level, but also on a national and global level. The current impacts caused by human actions on ecosystems on the frontiers are varied: indiscriminate deforestation, illegal logging, in addition to unlawful mining activities. Within this context, the main aim of this article is to discuss the process of primitive accumulation and the development of capital under the logic of expansion and appropriation of natural resources on the frontiers of the Brazilian and Venezuelan Amazon. In order to achieve this, the article will use a deductive-inductive approach combined with exploratory qualitative research. The main conclusion is that the fragmentation of the Amazon forest, into a landscape made up of small sections, has contributed to a reduction in the biodiversity through a wide variety of mechanisms, including the practice of deforestation, logging and mining, many of which are carried out illegally, criminally and most often in frontier areas. This has come about because the structure of these societies in frontier territories tends to be “dominated” and “influenced” within the terms that the ideology of capital imposes, including resorting to methods of primitive accumulation. Therefore, the frontier must be understood in its most comprehensive form as a social relation of production, or rather, as an essentially capitalist social relation of production